A rare case of malignant melanoma presenting as anterior-superior mediastinal mass - Dario Familiari, MD; Silvana Parisi, MD; Rossana Rizzo, MD; Elena Valenti, MD; Flavia Nunnari, MD; Michele Sibilio, MD; Rosario Marando, MD; Giancarlo Pino, MD; Francesco Monaco, MD (Radiology Case Reports)
Mediastinum, as site for malignant melanoma, is extremely rare, both as a primary or metastatic lesion. We present an extremely rare case of primary melanoma presenting as an anterior-superior mediastinal mass in a 65 years-old woman who went to the hospital for neurological symptoms due to unknown metastatic brain melanomas.